All means all what is it about me you can't teach? - Rodriguez, Eleanor Renée; TeachStream (Firm) (Sandy, Utah. : TeachStream : Video Journal of Education, 2002)
To close the achievement gap, all educators must understand that all students have the right to learn at high levels. Through the five E's of education: exposure, Experience, Expectations, Enduring Understandings, and Ethusiasm, students are not left asking,'What is it about me you can't teach?''
Volume Eleven, Issue 4, 1104S on container spine
Title from title screen
Featuring Eleanor Renee Rodriguez
Keywords: Teaching -- Instruction and study; Active learning; Educational evaluation